Cross-Cultural Service Learning as Pedagogy for Character Development in Occupational Therapy Doctoral Students - Heather Y.Z. St. Peters; Nathan Short (Scholarworks @ WMU, 2018)
Occupational therapists must demonstrate a broad spectrum of knowledge, clinical reasoning skills, and professionalism to be effective practitioners. Development of ethical practice must begin with the educational process to shape character traits as building blocks of moral reasoning. This article puts forth a cross-cultural service learning curricular module as lived experience for development of character traits in occupational therapy students. This mixed methods study investigated lived experience in the form of cross-cultural service learning as a pedagogy for development of character traits, as measured by the CIVIC, necessary to navigate professional ethical standards. Findings suggest a cross-cultural lived experience for occupational therapy doctoral students providing seating and mobility services in Guatemala significantly impacted character traits associated with professional ethical standards. Similar lived experience embedded in an occupational therapy curriculum may contribute to character development to guide ethical practice for the next generation of occupational therapists.